Custom prosthetic rehabilitation of ocular defect in elderly - Erriza, Vania; Sri Budi Barunawati; Titik Ismiyati; Intan Ruspita (Indonesia Prosthodontic Association, 2025)
Eye loss may cause deformities on patient's face that furthermore affect their psychosocial state. Ocular prosthesis is found to be effective to rehabilitate patients with eye loss due to trauma, congenital eye defect, tumor, or surgery. Elderly patients have special needs and limitations, such as communication, financial status, and access to healthcare providers. Through this case report, we present a successful fabrication of custom-made ocular prosthesis for elderly patient following right oculi enucleation. A 71-year-old male patient came with chief complaint of losing his old ocular prosthesis and wanted a new one. Initial impression was made with irreversible hydrocolloid. Final impression of patient's eye socket was made using individual custom tray and light body addition silicone impression material. A wax model was made and tried on patient, then processed with white acrylic resin to match patient's contralateral sclera color. Iris and pupil positioning were done, and ocular prosthesis was drawn to match patient's contralateral eye. The patient was satisfied with his new custom-made ocular prosthesis because of better fitting, comfort, and aesthetics compared to his old fabricated ocular prosthesis. Ocular prosthetic rehabilitation in elderly is associated with improvement of psychosocial status which leads to better quality of life. Keywords: ocular defect, custom prosthetic, ocular prosthesis, elderly